Islamic Education In The Merdeka Belajar Curriculum - Yuli Supriani; Asep Supriyadi; Bambang Samsul Arifin; Uus Ruswandi (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine Islamic religious education in the independent learning curriculum. The method used in this study uses a library method or approach, that literature or literature study can be interpreted as a series of activities related to methods of collecting library data, reading and recording and processing research materials. The results of this study indicate that the concept of